The Practices of Treating Deep Carious Lesions Compared with the Dental Curriculum in Turkish Dentistry - Kerimova, Leyla; Karabulut, Erdem; Yamanel, Kivanç; Arhun, Neslihan (Journal of Dentistry Indonesia, 2022)
Objective: The aim of this cross-sectional study is to investigate Turkish dentists’ opinions and preferences regarding the management of deep carious lesions and compare them with modern dental education concepts as provided by dental schools. Methods: Questionnaire 1 and Questionnaire 2 were sent separately to dental practitioners via the Turkish Dental Association and to university department heads of restorative dentistry. The data obtained were analyzed using chi-square tests and one-way ANOVA tests (p < 0.05). Results: Regarding Questionnaire 1, most of the dentists (89.3%) responded that caries lesions should be removed completely up to the hard cut-off condition of the cavity floor. There was a statistically significant difference between female and male dentists’ preferences on less invasive treatment (p < 0.05). Female dentists prefer less invasive treatment compared with male dentists (p = 0.002). Relatively older dentists (mean age = 41.8) are more inclined towards complete caries removal even if pulp exposure is likely (p = 0.040). The results of Questionnaire 2 reveal that there is no association between the time spans of education at dental schools and their caries removal approach curriculum (p > 0.05). Most department heads of restorative dentistry prefer to apply complete caries removal (78.5%, n = 51). Conclusion: Despite today’s curriculum encouraging less invasive caries removal techniques, most dentists prefer more invasive treatment options. Continuous education of contemporary dentistry could update these clinical treatment attitudes of dentists and improve their clinical practice.